TO THE ISSUE OF THE PRECONDITIONS FOR THE DEVELOPMENT OF SOCIAL ADAPTATION OF CHILDREN WITH A DEEP DEGREE OF MENTAL RETARDATION IN A SPECIALIZED ORPHANAGE (EDUCATION IN THE 21ST CENTURY, 2023)
This article discusses the issues of creating the preconditions for the development of social adaptation of children with a deep degree of mental retardation in a specialized orphanage, as nowadays the development of social adaptation of children with developmental disabilities is being of particular relevance. The success of social adaptation mainly depends on the correct organization and implementation of work on the development of those skills and abilities in this contingent of children in a specialized orphanage.The practice shows that an insufficiently clear definition and creation of prerequisites for the development of social adaptation of children with a deep degree of mental retardation complicates the effectiveness of organizing and conducting practical works of the formation and development of social adaption skills and abilities in these children in a specialized orphanage. Therefore, the creation of prerequisites for the development of social adaptation of children with a deep degree of mental retardation will help to carry out this work with this contingent of children in a specialized orphanage in a correct and effective way.The foregoing determines the importance of the problem under consideration, its theoretical, practical and social significance.On the basis of study and analysis of special scientific and methodological literature of this issue on research and analysis of the best practice and work experience of educators, teachers and psychologists of a specialized orphanage; the present article highlights the main directions of creating the prerequisites for the formation and development of social adaptation of children with a deep degree of mental retardation in terms of this institution.
Keywords: Key words: children with severe mental retardation, social adaptation, education, training, development, prerequisites, special teachers, educators.